PELATIHAN DAN IMPLEMENTASI PEMBELAJARAN BERBASIS ETNOSAINS DENGAN PENDEKATAN DEEP LEARNING - Matitaputty, Christi; Pradana, Sendy Putra; Tuapattinaya, Prelly M J; Palisoa, Napsin; Tuaputty, Hasan; Syahrul, Muhammad; Hehakaya, Wisye (PAKEM: Jurnal Pengabdian Kepada Masyarakat, 2026)
Science education in island regions, particularly in Salahutu District, Central Maluku Regency, faces challenges in developing contextual learning that reflects local potential. Many science teachers have not yet integrated ethnoscience elements and deep learning approaches into their teaching materials. This community service program aimed to enhance teachers’ capacity through training and mentoring in the development and implementation of deep learning–based ethnoscience teaching materials. The method used was a participatory–collaborative approach in the training and implementation of ethnoscience-based learning, which included the stages of preparation, training, implementation, and reflection. In the initial stage, the lecturer team conducted observations and interviews in several junior high schools in Salahutu to identify teachers’ needs and to design contextual training materials and learning tools. The training was carried out through workshops on developing teaching modules, learning materials, and student worksheets (LKPD), followed by mentoring during classroom implementation. The results indicated an improvement in teachers’ understanding and skills in integrating local natural and cultural potentials into science learning. Evaluation through questionnaires, reflections, and student interviews revealed that this approach fostered more meaningful, contextual, and relevant learning experiences. Overall, the program contributed to strengthening science teachers’ professionalism and enriching culturally responsive educational practices in island-based learning contexts